Usos do modo subjuntivo no Português brasileiro - Felicíssimo, Alice (2015)
This paper describes the occurrences of the Subjunctive Mode with the notion of futurity, to express the not factual and the variation of the present subjunctive mode by use of the present Indicative Mode. The research is based on principles of linguistic functionalism and has as a starting point the grammatical rules of the normative standard proposed by Brazilian traditional grammarians. The use of Subjunctive Mode, as the variation, was studied from the perspective of the emergent grammar of Givón, focused on grammar for communication and that emerges from communicative purposes shaping the discourse. We considered as a dependent variable of verbal mode, for understanding the phenomenon of alternation between subjunctive and indicative mode, the linguistic aspects: type of clause, verbal choice of main clause and verbal tense of the occurrence (the subordinate clause or independent clause). The sememe of futurity, identified in the propositional level, tends to preserve the use of the subjunctive mode, according to the normative standard grammar, and is used by speakers of medium and high level of education. For the use of the Indicative Mode with the imperative function, we found out that the selection of verbal morphology is under pressure of pragmatic-discursive relationship. The Indicative Mode serves to express the Imperative Mode, not containing the "order". This usage occurs in Brazilian Portuguese with speakers of all levels of education in face-to-face situations and with proximity. In subordinate clauses the modality of certainty of who speaks, even if it refers to future tense, propitiates the use of the Indicative Mode. This variation also occurs with speakers of all levels of education